ANALISIS PENANAMAN MODAL ASING DAN EKSPOR TERHADAP PRODUK DOMESTIK BRUTO SEKTOR INDUSTRI DI INDONESIA - iqfina harun; cut putri mellita sari (JURNAL EKONOMIKA INDONESIA, 2021)
This study aims to determine the effect of foreign investment and exports on GDP in the industrial sector in Indonesia. The data used in this study are secondary data from 2010 to 2018. The data analysis method used in this research is multiple linear regression analysis. The results show that foreign investment and exports have a positive and significant effect on the GDP of the Indonesian industrial sectorKeywords:Gross Domestic Product, Foreign Investment, Export